CYP2C8 and CYP2C9 mRNA expression profile in the human fetus - Johansson, Maria; Strahm, Emmanuel; Rane, Anders; Ekström, Lena (Frontiers in Genetics, 2014)
CYP2C8 and CYP2C9 are involved in the inactivation of several NSAIDs, including ibuprofen. CYP2C9 is the major form in human liver whereas CYP2C8 has been proposed to be the main CYP2C enzyme in fetal liver. The protein expression of CYP2C9 in the first trimester is low, only about 1% of the adult values, whereas the mRNA levels of CYP2C8/9 have not been determined at the fetal stage. In this study the mRNA expression levels of CYP2C8 and CYP2C9 were determined in 20 adult and 60 fetal liver tissue specimens. The expression profiles in fetal kidneys (n = 43), adrenals (n = 46), and lungs (n = 37) were also determined. Moreover the activity against ibuprofen hydroxylation was a determined in fetus and adult liver microsomes. Adult liver samples expressed 140 and 400 times higher levels of CYP2C8 and CYP2C9 mRNA, respectively as compared to fetal liver samples. Consistent with this, the hydroxylation of ibuprofen was 40 times higher in the adult liver microsomes. Hepatic CYP2C8 mRNA was three times more abundant than CYP2C9 mRNA in the fetus. Moreover, CYP2C8 were consistently expressed in all fetal tissues investigated, whereas CYP2C9 gene expression was confined to the liver in fetuses. Our results indicate that CYP2C8 plays a more important physiological role than CYP2C9 in the first trimester.